A mechanism for evaluating and forecasting the financial stability of an enterprise - T. V. Piatak; I. A. Fedorenko (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет, 2024)
During of the study, a mechanism for evaluating and forecasting the financial stability of an enterprise based on a process approach has been proposed. The created mechanism provides for modeling the financial sustainability of enterprise using an integrated model of the functional and structural organization of enterprise, which allows to establish the necessary relationships between the structural units of enterprise in the course of production cycles. It has been proposed to consider the financial stability of an enterprise in a broad and narrow sense for each production cycle during of its implementation. In the narrow sense, the financial stability of an enterprise has been considered as the ability to ensure solvency for current obligations at the expense of own and borrowed funds. In the broad sense, it has been proposed to consider financial stability as a process of repeatability of production cycles with control over the ratio of positive and negative cash flows in the dynamics. In the whole enterprise, financial stability has been proposed to be defined as the weighted average ratio of positive and negative cash flows. The use of this mechanism involves selecting the optimal number and value of factors that affect the planned financial result in the future by the method of successive approximations. The process approach involves the use of a model of the functional-structural organization of the enterprise to obtain the distribution of production cycles according to its optimal structure. The optimal structure is the functional-necessary structure, which contains the minimum set of elements of the production structure that ensures the execution of all production cycles with the duration determined in the mono-mode. The preparatory stage for building the functional-necessary structure is the normalization procedure, which ensures the determination of the conditions of connection between individual elements of the production cycle. For each production cycle, a set of absolute and relative financial indicators is established that have optimal values and determine the type of financial stability of the enterprise as a whole. It has been proposed to determine the type of financial stability of an enterprise as a whole by obtaining probabilities of financial stability for each production cycle, taking into account the share of the enterprise’s resources that is directed to the implementation of a specified production cycle.